Two decades of vaccine innovations for global public good: Report of the Developing Countries’ Vaccine Manufacturers Network 20th meeting, 21–23 october 2019, Rio de Janeiro, Brazil - Pagliusi, Sonia (Vaccine, 2020)
The Developing Countries’ Vaccine Manufacturers Network, joined by global health organizations, held its 20th meeting celebrating two decades of vaccine innovations for global public good. Health leaders from industry, academia and global health organizations reviewed efforts to accelerate innovation, improve access to vaccines, overcome inequalities and strengthen technological and public-health management capabilities. Discussion topics included World Health Organization’s immunization strategy, Pan American Health Organization’s system-strengthening efforts, Gavi’s evaluation of vaccine coverage in middle income countries and developments on public-market intelligence. Health market trends, delivery gaps, integration of system-wide needs, costs and benefits, and implications for stakeholder decision-making were areas of focus. Novel thinking was discussed on integration of policy, financing, regulatory pathways and alignment of innovation priorities to improve efficiency in vaccine development pathways. The Vaccine Innovation Prioritization Strategy collaboration presented nine global innovation priorities, and many other partners and members presented updates on their priorities. Novel technologies and platforms, such as RNA-based vaccines, adenoviral vectors, bioconjugation, blow-fill-seal and two-dimensional barcodes, provided opportunities to accelerate vaccine innovations. Challenges in planning and operations at global level included those in health security, polio eradication, re-emergence of diseases, disparities between forecasts and orders and heterogeneous regulatory requirements. Manufacturers were urged to accelerate innovation and prequalification of high-impact vaccines, such as pneumococcal, human papillomavirus and rotavirus vaccines, to strengthen immunization globally.